S6 Timing of pneumothorax post-CT-guided thoracic biopsy in a tertiary referral centre: implications for the ambulatory pneumothorax pathway. (11th November 2022) - Vella, C; Majid, M; Balasundaram, K; Hadani, S; Azam, R; Sudhir, R; Panchal, R; Das, I; Agrawal, S; Bennett, JA; Tufail, M
Abstract : CT-guided percutaneous biopsy (CTGB) is an important diagnostic modality in thoracic disease, and carries a 25% risk of pneumothorax. 1 Ambulatory pneumothorax management with early discharge is increasingly endorsed post-iatrogenic pneumothorax. This study aims to determine whether observation for 2 hours after CTGB is needed, by looking at the incidence of 'delayed' pneumothorax requiring intervention in a tertiary centre performing complex procedures. Method: Online records were used to recruit all patients undergoing CTGB in Glenfield Hospital, Leicester, a tertiary centre staffed by a team of specialist thoracic radiologists, from 15/03/2017–15/03/2021. Records were analysed for demographic data, size and location of biopsy target, timing of post-procedure pneumothorax as delineated on CTGB report or post-procedure chest X-ray (CXR), and intervention required. Delayed pneumothorax was defined as any pneumothorax diagnosed at 2 hours or later following CTGB. Results: 641 patients underwent CTGB during the 4-year study period. Characteristics are summarised in table 1 . Of these, 223 (34.8%) developed post-procedure pneumothorax. Of the 223, 83.4% were diagnosed during the procedure, and 37 (16.6%) were delayed-onset. No patients were admitted with a diagnosis of pneumothorax after a negative 2-hour check CXR. 79/223 (35%) of all pneumothoraces required intervention. 33.63% of immediate-onset pneumothoraces required intervention, the majority of which was on-table aspiration, compared to 10.8% of the delayed-onset group. The number of delayed-onset pneumothorax patients requiring intervention totalled 0.6% of the total study population. Conclusions: This study demonstrates that the incidence of delayed-onset pneumothorax requiring intervention is low in a tertiary centre setting. The optimal time for patient observation post-CTGB remains unknown. The authors acknowledge a high incidence of pneumothorax in the study cohort, which they postulate may be due to a higher volume of complex procedures in a tertiary setting, higher sensitivity of CT for reporting trivial post-biopsy pneumothorax, and the diversion of more complex lung cancer patients to the CTGB route during the COVID pandemic to avoid aerosol-generating procedures. Reference: Heerink WJ, de Bock GH, de Jonge GJ, Groen HJ, Vliegenthart R, Oudkerk M. Complication rates of CT-guided transthoracic lung biopsy: meta-analysis. Eur Radiol 2017;Jan;27 (1):138–148.